2017
DOI: 10.1159/000485759
|View full text |Cite
|
Sign up to set email alerts
|

Fstl1 Promotes Glioma Growth Through the BMP4/Smad1/5/8 Signaling Pathway

et al.

Abstract: Background: Gliomas result in the highest morbidity and mortality rates of intracranial primary central nervous system tumors because of their aggressive growth characteristics and high postoperative recurrence. They are characterized by genetic instability, intratumoral histopathological variability and unpredictable clinical behavior in patients. Proliferation is a key aspect of the clinical progression of malignant gliomas, complicating complete surgical resection and enabling tumor regrowth and further pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Apart from this, upregulation of FSTL1, a homolog of FSTL3, increased the TMZ resistance of GBM cells [67] and was correlated with proliferation and colony formation [68]. FSTL3 is a secreted glycoprotein involved in the regulation of various biological effects through its binding to members of the TGFβ superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, upregulation of FSTL1, a homolog of FSTL3, increased the TMZ resistance of GBM cells [67] and was correlated with proliferation and colony formation [68]. FSTL3 is a secreted glycoprotein involved in the regulation of various biological effects through its binding to members of the TGFβ superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…For SMAD5, it has been reported that miR-145 can promote the migration and migration of esophageal cancer cells by inhibiting the expression of SMAD5 [40]. Fstl1 can promote glioma growth through SMAD1 / SMAD5 / SMAD8 [41]. At the same time, SMAD5 expression increases in prostate cancer, which is closely related to postoperative survival [40].…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] Fstl1 can promote glioma growth through SMAD1/SMAD5/SMAD8. [ 40 ] At the same time, SMAD5 expression increases in prostate cancer, which is closely related to postoperative survival. [ 39 ] For the SMAD6 gene, high expression of it can promote the development of glioma.…”
Section: Discussionmentioning
confidence: 99%